Red-blood-cell-membrane-enveloped magnetic nanoclusters as a biomimetic theranostic nanoplatform for bimodal imaging-guided cancer photothermal therapy. Issue 4 (6th January 2020) - Wang, Sheng; Yin, Yipengchen; Song, Wang; Zhang, Qin; Yang, Zhijuan; Dong, Ziliang; Xu, Ye; Cai, Sanjun; Wang, Kuang; Yang, Wuli; Wang, Xuejun; Pang, Zhiqing; et al.
Abstract : Biomimetic Cyp-MNC@RBCs with high tumor homing capacity are utilized as promising nanotheranostics, enabling bimodal imaging-guided cancer photothermal therapy. Abstract : The use of red blood cell (RBC) membrane coatings has recently been found to be a biomimetic strategy to confer inner core nanomaterials with improved pharmacokinetic profiles by utilizing the intrinsic long blood circulation time of RBCs. Here, we envelope superparamagnetic nanoclusters (MNCs) with RBC membrane ghosts to obtain MNC@RBCs with significantly improved physiological stability compared to that of bare MNCs. After being loaded with near-infrared (NIR) cypate molecules, the as-prepared Cyp-MNC@RBCs show remarkably increased NIR absorbance and resultant efficient photothermal conversion efficacy. By tracking the NIR fluorescence of cypate in an in vivo fluorescence imaging system, we uncover that such Cyp-MNC@RBCs upon intravenous injection show significantly improved tumor-homing capacity as compared to bare cypate-loaded MNCs. A similar result is further evidenced by recording the T 2 -weighted magnetic resonance imaging (MRI) signal of MNCs. Furthermore, upon exposure to 808 nm laser irradiation, the tumors grown on the mice with the intravenous injection of Cyp-MNC@RBCs show a higher temperature increase than the tumors grown on the mice injected with plain MNC@RBCs and thus are significantly suppressed via photothermal ablation. This study presents the preparation of biomimetic Cyp-MNC@RBCs with greatly improved tumor-homing capacity as multifunctional nanotheranostic agents for fluorescence and MRI bimodal imaging-guided cancer photothermal therapy.